2015
DOI: 10.1016/j.ijid.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Human melioidosis reported by ProMED

Abstract: HighlightsProMED would be used to assess the reliability of the data of emerging infectious diseases, such as melioidosis.The study evaluated the effectiveness of ProMED as a source of epidemiological data by focusing on melioidosis.This work identified 4630 cases of melioidosis with an overall case fatality rate of 11%, mainly reported from Australia, Thailand, Singapore, Vietnam, and Malaysia.Although certain areas need to be improved, ProMED provided good information about melioidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
(52 reference statements)
0
13
0
1
Order By: Relevance
“…Although ProMED proved to be a useful source of information about coronavirus, it was evident that it gave a misleading impression of the distribution and mortality in some areas, as has been previously reported for other infections [15]. We think it would be useful to consider the adoption of standardized templates for reporting to ProMED in order to enhance the standardization of data and provide clear, accurate and reliable information that could be used in conducting epidemiological analyses to establish the status of emerging diseases and assist in their recognition and control, as has been previously suggested [23]. Besides, we think it would be useful for reports in one language to be mirrored to ProMED in other languages, especially when it is the language of the country from which the report originated.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Although ProMED proved to be a useful source of information about coronavirus, it was evident that it gave a misleading impression of the distribution and mortality in some areas, as has been previously reported for other infections [15]. We think it would be useful to consider the adoption of standardized templates for reporting to ProMED in order to enhance the standardization of data and provide clear, accurate and reliable information that could be used in conducting epidemiological analyses to establish the status of emerging diseases and assist in their recognition and control, as has been previously suggested [23]. Besides, we think it would be useful for reports in one language to be mirrored to ProMED in other languages, especially when it is the language of the country from which the report originated.…”
Section: Discussionmentioning
confidence: 70%
“…When compared with the information provided by reports in the subject literature, the most notable finding was that the CFR identifiable from ProMED was low in comparison with the published literature 10% for SARS-CoV and 37% for MERS-CoV. The coronaviruses already identified might only be the tip of the iceberg, with potentially more novel and severe zoonotic events to be revealed [1], but under-reporting of fatal cases by ProMED is not surprising, as the purpose is to act as an early alert system, and outcomes may not be known at the time of posting [23]. Besides, the data were incomplete with regards to characteristics such as gender, age and occupation (last, no analyzed).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…While predominantly prevalent in Southeast Asia and Northern Australia, there is increasing evidence that its distribution in tropical areas is much larger than previously thought [1,2]. If Western infectious disease specialists were asked to provide snapshot information on this rare condition, those most informed would probably answer that it sporadically affects travelers, mainly those with underlying illness (in particular diabetes mellitus) after environmental exposure in Southeast Asia, and that the disease may have various, often severe, manifestations and requires a rather complex and prolonged treatment.…”
mentioning
confidence: 91%
“…Katherinn et al focused on human melioidosis to evaluate the utility of ProMED for infection control. They observed that ProMED provided daily reports of melioidosis occurrence which helped healthcare workers manage to control the diseases [4]. Besides, Ince et al assessed the reports related to Crimean-Congo haemorrhagic fever virus and validated ProMED as a platform for integrating news of different sources [5].…”
Section: Introductionmentioning
confidence: 99%